2017
DOI: 10.1155/2017/8494107
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Supplementation Lowers Oxidative Stress and Regulates Adipokines in Obese Patients on a Calorie‐Restricted Diet

Abstract: Obesity is one of the major global health problems. Melatonin deficiency has been demonstrated to correlate with obesity. The aim of the study was to estimate the effect of melatonin on oxidative stress and adipokine levels in obese patients on a calorie-restricted diet. Thirty obese patients were supplemented with a daily dose of 10 mg of melatonin (n = 15) or placebo (n = 15) for 30 days with a calorie-restricted diet. Serum levels of melatonin, 4-hydroxynonenal (HNE), adiponectin, omentin-1, leptin, and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 98 publications
1
59
0
2
Order By: Relevance
“…Melatonin administration has been correlated to the enhancement of the plasmatic antioxidant capacity in both animal models and human studies [77]. In general, melatonin intake is associated with diminished oxidative stress [78]. The supplementation with melatonin can be beneficial, beyond oxidative stress, in the reduction of inflammation, hypertension, and other metabolic syndrome-related markers [77].…”
Section: Administration Of Lentil Sprouts Enhances Plasmatic Antioxidmentioning
confidence: 99%
“…Melatonin administration has been correlated to the enhancement of the plasmatic antioxidant capacity in both animal models and human studies [77]. In general, melatonin intake is associated with diminished oxidative stress [78]. The supplementation with melatonin can be beneficial, beyond oxidative stress, in the reduction of inflammation, hypertension, and other metabolic syndrome-related markers [77].…”
Section: Administration Of Lentil Sprouts Enhances Plasmatic Antioxidmentioning
confidence: 99%
“…Pineal melatonin synthesis/secretion is stimulated by darkness and inhibited by exposure to light [12]. Intervention studies reported that melatonin can improve lipid profile [13], glycemic status [14], immune system function [15], anti-oxidative status [16], and inflammatory parameters [17]. In addition, some studies introduced melatonin as a potential BP regulator [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…<30-50 lux). 21 This nocturnal hormone is known for impacting seasonal and circadian rhythms, 22 promoting sleep onset, influencing core body temperature (CBT), and following a 24-hour light-dark cycle. 17 In particular, the enzymes involved in synthesizing melatonin are stimulated by darkness and inhibited by light.…”
Section: Melatoninmentioning
confidence: 99%